2015
DOI: 10.1007/s11468-015-9969-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Nanoplasmonic Biosensor Sensitivity with Orientated Single Domain Antibodies

Abstract: Localized surface plasmon resonance (LSPR) spectroscopy and imaging are emerging biosensor technologies which tout label-free biomolecule detection at the nanoscale and ease of integration with standard microscopy setups. The applicability of these techniques can be limited by the restrictions that surface-conjugated ligands must be both sufficiently small and orientated to meet analyte sensitivity requirements. We demonstrate that orientated single domain antibodies (sdAb) can optimize nanoplasmonic sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The addition of a positive tail was expected to facilitate the directional immobilization of sdAbs onto the negatively charged microsphere surface and thus improve the detection limits in that manner as well [ 39 ], unfortunately, we did not see the GSKKK fusion achieve this result. The cause of this is unclear, but perhaps the sdAb’s binding site on the GP is difficult for the surface immobilized sdAb to access efficiently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of a positive tail was expected to facilitate the directional immobilization of sdAbs onto the negatively charged microsphere surface and thus improve the detection limits in that manner as well [ 39 ], unfortunately, we did not see the GSKKK fusion achieve this result. The cause of this is unclear, but perhaps the sdAb’s binding site on the GP is difficult for the surface immobilized sdAb to access efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…A lysine-containing tail termed GSKKK (GGGGSGGGGKKK) was fused to the C-terminus of the sdAbs aiming to either increase biotin incorporation for use as the detection molecule or to enhance directional immobilization onto the surface to improve the percentage of active antibody attached, with the goal of improving the detection limits for GP/VLP (Fig. 2 d) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The RZ fragments flanked with a XhoI site at both ends were amplified from the original vector using PCR and inserted to the XhoI site within D12f-pET22b. D12f-RZ [33] then served as a template to insert a 10 amino acid Gly-Ser linker (L10, GGGGSGGGGS) using the Quikchange II mutagenesis kit and minor modifications to the manufacturer’s protocol (Agilent Technologies; Santa Clara, CA). Mutagenesis was achieved using the forward primer, 5′- GCGGCCGCACTCGAGGGCGGTGGCGGTAGCGGCGGTGGCGGTTCTTTTGATGCGTCCAATTTTAAA-3′, and its reverse complement sequence as the reverse primer.…”
Section: Methodsmentioning
confidence: 99%
“…Improving CEA detection sensitivity will require high affinity ligands which are readily produced, resistant to denaturation, and can be orientated to optimize the probability of capture. Conventional antibodies (Abs) are the current detection ligands of choice, and while they exhibit the necessary specificity and affinity, it is not uncommon to find that only 10% or less of those conjugated to the sensor surface can actively bind analyte ( Raphael et al, 2015 ). This loss of activity can be a result of incorrect orientation, denaturation due to multi-point attachment, as well as steric hindrances (or combinations of the above).…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular importance on nanosensor platforms with limited sensor surface area. The smaller size and ability to orient sdAbs has been shown to improve signal to noise ratios compared to that of conventional Abs when used to functionalized nanoplasmonic sensors ( Raphael et al, 2015 ) as well as on larger commercial surface plasmon resonance (SPR) formats ( Della Pia and Martinez, 2015 ). The later study demonstrated that with the same density of sdAbs and conventional Abs on a SPR chip, sdAbs had a lower limit of detection, suggesting that immobilized sdAbs can access binding pockets better than immobilized conventional Abs.…”
Section: Introductionmentioning
confidence: 99%